Unveiling the Impact of Social Expectations on Psychological Distress among Graduates in Bangladesh - Oliul Islam, Md.; Hafizur Rahman, Md.; Bari Chowdhuri, Abu Sayef Md Muntaquimul (Jahangirnagar University Journal of Management Research, 2026)
This study aimed to unveil the impacts of social expectations (SE) on psychological distress (PD) among graduates in Bangladesh. This study is inspired by the Social Identity Theory (SIT), which develops self-concepts of a member of society and directs them to fulfill social expectations. A quantitative approach was adopted and an online survey method incorporating a five-point Likert scale questionnaire containing 31 items of five independent constructs of SE - family expectations (FE), social norms (SN), gender expectations (GE), academic performance (AP), career expectations (CE) on the outcome variable PD. A convenient sampling method was employed to collect data from 251 university graduates. Structural equation modeling (PLS-SEM) has been utilized to measure reliability, validity, and test the hypotheses. The study revealed a statistically significant impact of SE on PD. The study suggested fostering resilience and coping skills to deal with social expectations to mitigate negative psychological impacts.